Effectiveness of an organized training module on proficiency regarding the POSH Act among students of a selected degree college in Bhopal - Rajratan; Trivesh Goswami; Lily Podder; Shikha Dwivedi; Shalini Kumari; Saraswati Limbu; Saritha Chaudhary; Shambhavi; Shama; Seema (Future Health, 2026)
Objective Sexual harassment is a serious social and legal issue that affects individuals in workplaces and educational institutions, violating the fundamental rights to dignity, equality, and safety. It includes any unwelcome conduct of a sexual nature, such as physical advances, sexually colored remarks, requests for sexual favors, display of obscene material, or inappropriate verbal and non-verbal behavior that creates a hostile environment. The aim is to aware the degree college students regarding the Prevention of Sexual Harassment (POSH) Act through an organized training module. Despite the enactment of the Sexual Harassment of Women at Workplace (Prevention, Prohibition and Redressal) Act, 2013, awareness regarding its provisions and grievance redressal mechanisms remains inadequate among students, leading to underreporting and ineffective implementation. Material and Methods A quantitative quasi-experimental pre-test post-test control group design was adopted to evaluate the effectiveness of an organized training module on POSH Act proficiency among undergraduate students of a selected degree college in Bhopal. A total of 320 students were selected using purposive sampling. Two groups were formed, the experimental (n = 160) and control (n = 160) groups. Data were collected using a self-structured questionnaire comprising socio-demographic variables and 21 questions assessing proficiency regarding the POSH Act. The experimental group received a structured training module covering key provisions, like what sexual harassment is, its types, preamble, what a workplace is, aggrieved women, internal complaints committee composition, complaint procedures, and penalties, etc., while the control group received no intervention. Data were analyzed using SPSS V.26, and the McNemar-Bowker Chi-square test was applied to determine effectiveness. Results At baseline, most participants demonstrated average proficiency levels. Following the intervention, the experimental group showed significant improvement, with 60% achieving high proficiency in the post-test and no participants remaining in the low category. The improvement was statistically significant ( p